Political Marketing Strategy: Efforts of Regional Head Candidates to Attract the Sympathy of Voters in Wajo Regency - Sudarsono (Jurnal Bina Praja, 2024)
This study aims to analyze the most effective communication strategies, personal branding, social media utilization, and data-driven campaign methods in influencing public opinion and mobilizing support. Qualitative descriptive research methods were employed to collect data through in-depth interviews, direct observation, and the analysis of documents pertinent to political campaigns. The result showed that the primary strategies employed by regional head candidates encompass the construction of a favorable image, placing campaign props in pivotal locations, and adapting campaign messages to align with the region's social, cultural, and community characteristics. The strategic incorporation of marketing components can potentially enhance a candidate's probability of electoral success. Both candidates continue to construct a robust and favorable image, optimize the utilization of campaign props, leverage social media as a dynamic communication tool, and provide pertinent and engaging campaign content. It is imperative to acknowledge that this research is constrained by certain limitations, particularly concerning the data employed, which is contextual and region-specific. Consequently, the findings may be challenging to generalize to other regions with disparate social, cultural, and political attributes. Therefore, further research must be conducted to evaluate the influence of ethical and regulatory frameworks on the utilization of political marketing techniques, including matters about data privacy and misinformation. Such an approach will contribute to the advancement of a robust and flourishing democratic system.